Nanometer negative ion composite enhanced PVC wood-plastic plate and production process thereof

By adopting multi-layer structural design and synergistic effect of nano-negative ion materials and carrier materials in PVC wood-plastic boards, the shortcomings of traditional boards in antibacterial, deodorization and air purification are solved, and high-efficiency negative ion release and excellent mechanical properties are achieved.

CN119682344AInactive Publication Date: 2025-03-25ANHUI YINUO WOOD PLASTIC SHEET TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411856354.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PVC wood-plastic boards have shortcomings in antibacterial, deodorization, air purification, etc., and it is difficult to effectively apply nano-negative ion materials while maintaining the mechanical strength and other excellent properties of the boards.

Method used

Using a multi-layer structure design, the synergistic effect of nano-negative ion materials and carrier materials, the modification treatment of lignocellulosic materials, the application of laser hole drilling technology and the optimization of heat treatment processes, forming a composite structure of the bottom layer, intermediate layer and surface layer to achieve the improvement of negative ion release and mechanical properties.

Benefits of technology

It realizes multifunctional integration, efficient negative ion release, excellent mechanical properties and environmental sustainability, and improves the antibacterial, deodorizing and air purification performance of the board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119682344A_ABST
    Figure CN119682344A_ABST
Patent Text Reader

Abstract

The invention discloses a nanometer negative ion composite enhanced PVC wood-plastic plate and a production process thereof.The nanometer negative ion composite enhanced PVC wood-plastic plate comprises a bottom layer, a middle layer and a surface layer, the bottom layer is a mixture of PVC resin and a lignocellulose material and accounts for 30% of the total thickness, and the middle layer is a mixture of the PVC resin and the lignocellulose material; and the middle layer is a composite layer which is rich in nanometer negative ion materials and mixed with carrier materials and PVC resin, and accounts for 40% of the total thickness. According to the nano negative ion composite enhanced PVC wood-plastic plate and the production process thereof, each layer has different functions and characteristics, the bottom layer mainly provides mechanical strength and air permeability, the middle layer is rich in nano negative ion materials and carrier materials and is responsible for releasing negative ions and improving functionality, and the surface layer integrates multiple functional materials, so that the surface layer is beneficial to the environment protection. And it is ensured that the plate has excellent surface performance, and multifunctional integration, efficient negative ion release, excellent mechanical performance and environment-friendly sustainability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC wood-plastic board, in particular to a nano-anion composite enhanced PVC wood-plastic board and a production process thereof. Background Art

[0002] Although traditional PVC wood-plastic boards have good physical properties and weather resistance, they are deficient in antibacterial, deodorizing, and air purification. In recent years, as people's requirements for the quality of living environment continue to increase, the development of building materials with health functions has become a trend. Nano-anion materials have attracted attention due to their ability to release negative ions, improve air quality, and inhibit bacterial growth. However, it is still a challenge to effectively apply nano-anion materials to PVC wood-plastic boards while maintaining the mechanical strength and other excellent properties of the boards. Summary of the invention

[0003] The object of the present invention is to provide a nano-anion composite reinforced PVC wood-plastic board and a production process thereof, which realizes multifunctional integration, efficient anion release, excellent mechanical properties and environmental sustainability through multi-layer structure design, synergistic effect of nano-anion materials and carrier materials, modification of lignocellulose materials, application of laser drilling technology and optimization of heat treatment process, and solves the problems raised in the above-mentioned background technology.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a nano-anion composite enhanced PVC wood-plastic board, comprising a bottom layer, a middle layer and a surface layer, wherein the bottom layer is a mixture of PVC resin and wood cellulose material, accounting for 30% of the total thickness, the middle layer is a composite layer rich in nano-anion material and a carrier material mixed with PVC resin, accounting for 40% of the total thickness, the middle layer contains a fine microporous structure formed by a foaming process, and the surface layer is a mixture of PVC resin, wood cellulose material and functional material, accounting for 30% of the total thickness.

[0005] Preferably, the lignocellulose material is selected from at least one of wood powder, bamboo powder, rice husk powder, wheat straw powder, coconut shell powder, and cotton stalk powder. The lignocellulose is modified using a silane coupling agent before use. The modification method of the lignocellulose is as follows:

[0006] The lignocellulosic material is dried at a temperature of 80°C-120°C for 2-4 hours to remove surface moisture and ensure the subsequent modification effect. The lignocellulosic material is crushed into fine particles, and the particle size is generally controlled between 40-100 meshes to increase its specific surface area and improve the modification effect. The silane coupling agent is dissolved in an organic solvent and the concentration is controlled between 1%-5%. The dried lignocellulosic material is immersed in the silane coupling agent solution for 10-30 minutes to ensure that the surface of the material is fully in contact with the silane coupling agent. After immersion, the material is taken out and the excess liquid is absorbed with filter paper. The modified lignocellulosic material is heated at a temperature of 60°C-120°C for 1-3 hours to promote the silane coupling agent to react with the hydroxyl groups on the surface of the lignocellulosic material to form a stable chemical bond. The silane coupling agent is a class of compounds with bifunctional groups, one end of which can react with the hydroxyl groups on the surface of the lignocellulosic material, and the other end can chemically bond or physically adsorb with the PVC resin or other polymers, thereby improving the interfacial bonding force between the two.

[0007] Preferably, the nano negative ion material is at least one of tourmaline, tourmaline, zinc oxide, titanium dioxide, nano silver, nano copper, and rare earth elements.

[0008] Preferably, the carrier material includes at least one of activated carbon, mesoporous silica, zeolite, ceramic powder, cellulose-based material, polyurethane foam, carbon nanotubes, graphene, montmorillonite and glass fiber. The carrier material has a high specific surface area and good adsorption properties and can effectively load nano-anion materials.

[0009] Preferably, the functional material includes at least one of a photocatalyst, an anti-ultraviolet absorber, an antibacterial agent, a hydrophilic additive, a breathable additive and a conductive material.

[0010] Preferably, both the bottom layer and the surface layer are provided with a microporous structure, the microporous density is 5%-10%, and the micropore diameter is controlled between 10-50 microns. The microporous structure of the bottom layer cannot destroy its overall mechanical strength while improving the air permeability. The microporous structure of the surface layer improves the negative ion release efficiency and overall performance.

[0011] Preferably, the micropore density of the intermediate layer is about 30%-50%, and the micropore diameter is controlled between 1-10 microns to maximize the surface area and negative ion release efficiency.

[0012] Another technical problem to be solved by the present invention is to provide a production process of nano-anion composite reinforced PVC wood-plastic board, comprising the following steps:

[0013] Step 1: Mix the raw materials of the bottom layer, middle layer and surface layer separately, and control the temperature of the twin-screw extruder between 160℃-180℃ to ensure that all components are fully melted and evenly mixed;

[0014] Step 2: Use co-extrusion equipment to extrude the bottom layer, middle layer and surface layer materials at the same time, and form a multi-layer composite sheet through a co-extrusion die. After the molding is completed, it is gradually cooled to room temperature. Too fast cooling speed may cause internal stress concentration of the material, affecting the dimensional stability and mechanical properties of the product;

[0015] Step 3: For the formed bottom layer and surface layer, a microporous structure is formed on the surface or inside of the material by laser drilling;

[0016] Step 4: The formed sheet is trimmed and heat treated to ensure the appearance quality of the sheet. The heat treatment temperature is controlled at around 120°C for 20 minutes to enhance the functional performance of the material.

[0017] Preferably, the pressures of different extrusion layers of the co-extrusion equipment are: bottom layer: 1-5 MPa; middle layer: 1-3 MPa; surface layer: 1-3 MPa.

[0018] Preferably, the foaming agent used in the middle layer is a composite foaming agent of citric acid and sodium bicarbonate, and the added amount of the foaming agent is 1%-5% of the total amount of the raw materials of the middle layer.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The nano-anion composite reinforced PVC wood-plastic board and its production process proposed in the present invention adopt a three-layer structure design of a bottom layer, a middle layer and a surface layer, each layer has different functions and characteristics, the bottom layer mainly provides mechanical strength and air permeability, the middle layer is rich in nano-anion materials and carrier materials, responsible for releasing anions and improving functionality, and the surface layer integrates a variety of functional materials to ensure that the board has excellent surface properties. The middle layer adopts a fine microporous structure formed by a foaming process, which greatly increases the surface area of ​​the material and further improves the release efficiency of anions. This microporous structure not only helps the diffusion of anions, but also enhances the material The air permeability and moisture absorption of the material can improve the indoor air quality. The bottom layer and the surface layer are also provided with a microporous structure, which promotes the diffusion and release of negative ions. Through the modification of the silane coupling agent, the interface between the lignocellulose material and the PVC resin is more tightly bonded, reducing the influence of external factors such as moisture and oxygen on the material, and extending the service life of the board. Through the multi-layer structure design, the synergistic effect of nano-anion materials and carrier materials, the modification of lignocellulose materials, the application of laser drilling technology and the optimization of heat treatment process, multifunctional integration, efficient negative ion release, excellent mechanical properties and environmental sustainability are achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic cross-sectional view of the PVC wood-plastic board of the present invention.

[0022] In the figure: 1, bottom layer; 2, middle layer; 3, surface layer. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1:

[0025] In order to solve the existing problem of effectively applying nano-anion materials to PVC wood-plastic boards while maintaining the mechanical strength and other excellent properties of the boards, it is still a challenge. Figure 1 , this embodiment provides the following technical solutions:

[0026] The following materials by mass percentage were used for raw material mixing:

[0027] Bottom Layer 1:

[0028] PVC resin: 50%

[0029] Lignocellulosic material: wood powder 44%

[0030] Plasticizer: DOP2%

[0031] Stabilizer: Calcium zinc stabilizer 2%

[0032] Lubricant: Calcium stearate 1%

[0033] Coupling agent: silane coupling agent 1%;

[0034] Middle layer 2:

[0035] PVC resin: 74%

[0036] Nano negative ion material: rare earth element doped zinc oxide 8%

[0037] Support material: Zeolite 7%

[0038] Plasticizer: DOP2%

[0039] Stabilizer: Calcium zinc stabilizer 2%

[0040] Lubricant: Calcium stearate 1%

[0041] Coupling agent: silane coupling agent 1%

[0042] Foaming agent: 5% composite foaming agent of citric acid and sodium bicarbonate;

[0043] Surface 3:

[0044] PVC resin: 45%

[0045] Lignocellulosic material: bamboo powder 35%

[0046] Anti-ultraviolet absorber: photocatalyst titanium dioxide TiO2 10%

[0047] Silver ion antimicrobial agent: 4%

[0048] Plasticizer: DOP2%

[0049] Stabilizer: Calcium zinc stabilizer 2%

[0050] Lubricant: Calcium stearate 1%

[0051] Coupling agent: silane coupling agent 1%;

[0052] The lignocellulosic material is modified before use. The lignocellulosic material is dried at 100°C for 2 hours to remove surface moisture and ensure the subsequent modification effect. The lignocellulosic material is crushed into fine particles, and the particle size is generally controlled between 40-100 meshes to increase its specific surface area and improve the modification effect. An organic solvent is selected to dissolve the silane coupling agent, and the concentration is controlled at 2%. The dried lignocellulosic material is immersed in the silane coupling agent solution for 20 minutes to ensure that the surface of the material is fully in contact with the silane coupling agent. After immersion, the material is taken out and the excess liquid is absorbed with filter paper. The modified lignocellulosic material is heated at 100°C for 2 hours to promote the silane coupling agent to react with the hydroxyl groups on the surface of the lignocellulosic material to form a stable chemical bond. The silane coupling agent is a class of compounds with bifunctional groups, one end of which can react with the hydroxyl groups on the surface of the lignocellulosic material, and the other end can chemically bond or physically adsorb with the PVC resin or other polymers, thereby improving the interfacial bonding force between the two.

[0053] The above materials are mixed separately according to different layers, wherein the nanometer negative ion material, carrier material and foaming agent in the middle layer 2 are added in multiple times to improve the uniformity of mixing, and the uniformly mixed layers of materials are put into the co-extrusion equipment, and the materials of the bottom layer, the middle layer and the surface layer are extruded at the same time, and a multi-layer composite plate is formed through a co-extrusion die, wherein the bottom layer 1 accounts for 30% of the total thickness, the middle layer 2 accounts for 40% of the total thickness, and the surface layer 3 accounts for 30% of the total thickness, to ensure good adhesion and overall performance between the layers, and the temperature of the co-extrusion equipment is set to 170°C, and the layers during extrusion are The pressures are 4MPa for the bottom layer 1, 1MPa for the middle layer 2, and 2MPa for the surface layer 3. After forming, the sheet is immediately moved to a cooling device and gradually cooled to room temperature to avoid internal stress concentration. Laser drilling technology is used to form a microporous structure inside and on the surface of the bottom layer 1, and a microporous structure is formed inside the surface layer 3. The microporous density is 6%, and the microporous diameter is controlled at 25 microns. Laser drilling can ensure the integrity of the surface of the surface layer 3 without affecting the surface quality, and ensure that the micropores are evenly distributed inside the sheet, thereby improving the air permeability and negative ion release efficiency. The formed sheet is trimmed and polished to ensure a smooth and flat surface, and then subjected to heat treatment. Heat treatment can promote the transformation of TiO2 from an amorphous or low-crystallinity state to a high-crystallinity anatase phase or rutile phase, thereby improving its photocatalytic activity.

[0054] The wood-plastic board prepared by the above method was tested for performance and the following data were obtained:

[0055]

[0056]

[0057] The wood-plastic board prepared in this embodiment has high-efficiency antibacterial and anti-ultraviolet functions, is suitable for outdoor environments, has excellent antibacterial rate and anti-ultraviolet capabilities, and maintains good mechanical properties.

[0058] Embodiment 2:

[0059] The following materials by mass percentage were used for raw material mixing:

[0060] Bottom Layer 1:

[0061] PVC resin: 54%

[0062] Modified lignocellulosic material: rice husk powder 40%

[0063] Plasticizer: DOP2%

[0064] Stabilizer: Calcium zinc stabilizer 2%

[0065] Lubricant: Calcium stearate 1%

[0066] Coupling agent: silane coupling agent 1%;

[0067] Middle layer:

[0068] PVC resin: 71%

[0069] Nano negative ion material: Tourmaline 10%

[0070] Support material: mesoporous silica 8%

[0071] Plasticizer: DOP2%

[0072] Stabilizer: Calcium zinc stabilizer 2%

[0073] Lubricant: Calcium stearate 1%

[0074] Coupling agent: silane coupling agent 1%

[0075] Foaming agent: 5% composite foaming agent of citric acid and sodium bicarbonate

[0076] Surface 3:

[0077] PVC resin: 45%

[0078] Modified wood cellulose material: bamboo powder 34%

[0079] Hydrophilic additive: polyvinyl alcohol PVA 10%

[0080] Plasticizer: DOP2%

[0081] Stabilizer: Calcium zinc stabilizer 2%

[0082] Lubricant: Calcium stearate 1%

[0083] Coupling agent: silane coupling agent 1%

[0084] Air permeability additive: mesoporous silica 5%;

[0085] The wood-plastic board was processed by the same method as in Example 1, and the prepared wood-plastic board was tested for performance to obtain the following data:

[0086] Test items Test Method Test results Breathability ASTM D737 <![CDATA[10L / m 2 ·min]]> Negative ion release Negative ion detector <![CDATA[8000ions / cm 3 ]]> Tensile Strength GB / T 1040.2-2006 30MPa Bending Strength GB / T 9341-2008 55MPa Impact strength GB / T 1043.1-2008 <![CDATA[10kJ / m 2 ]]> Antimicrobial properties ISO 22196 Antibacterial rate>95% UV resistance ASTM G154 800 hours without noticeable fading or aging

[0087] The wood-plastic board prepared in this embodiment has high air permeability and negative ion release function, is suitable for indoor air purification, has efficient negative ion release ability and good air permeability, and is suitable for improving indoor air quality.

[0088] Embodiment 3:

[0089] The following materials by mass percentage were used for raw material mixing:

[0090] Bottom Layer 1:

[0091] PVC resin: 52%

[0092] Modified lignocellulosic material: wood powder 37%

[0093] Plasticizer: DOP 2%

[0094] Stabilizer: Calcium zinc stabilizer 2%

[0095] Lubricant: Calcium stearate 1%

[0096] Coupling agent: silane coupling agent 1%

[0097] Wear-resistant additive: Silicon carbide SiC5%

[0098] Middle layer 2:

[0099] PVC resin: 76%

[0100] Nano negative ion material: Tourmaline 8%

[0101] Carrier material: activated carbon 7%

[0102] Plasticizer: DOP2%

[0103] Stabilizer: Calcium zinc stabilizer 2%

[0104] Lubricant: Calcium stearate 1%

[0105] Coupling agent: silane coupling agent 1%

[0106] Foaming agent: 3% composite foaming agent of citric acid and sodium bicarbonate

[0107] Surface 3:

[0108] PVC resin: 45%

[0109] Modified wood cellulose material: bamboo powder 34%

[0110] Conductive material: Carbon black 10%

[0111] Plasticizer: DOP2%

[0112] Stabilizer: Calcium zinc stabilizer 2%

[0113] Lubricant: Calcium stearate 1%

[0114] Coupling agent: silane coupling agent 1%

[0115] Wear-resistant additives: Silicon carbide SiC5%;

[0116] The wood plastic board was processed by the same method as in Example 1, and the prepared wood plastic board was tested for performance to obtain the following data:

[0117] Test items Test Method Test results Wear resistance GB / T 3960-2008 Wear amount <0.05g Conductive properties GB / T 1410-2006 Resistivity <10^6Ω·cm Tensile Strength GB / T 1040.2-2006 40MPa Bending Strength GB / T 9341-2008 65MPa Impact strength GB / T 1043.1-2008 <![CDATA[15kJ / m 2 ]]> Negative ion release Negative ion detector <![CDATA[6000ions / cm 3 ]]> UV resistance ASTM G154 1000 hours without noticeable fading or aging

[0118] The wood-plastic board prepared in this embodiment has high wear resistance and conductive function, is suitable for industrial plants and laboratories, has excellent wear resistance and conductive properties, can effectively prevent static electricity accumulation, and ensure safety.

[0119] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0120] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. A nano-anion composite reinforced PVC wood-plastic board, comprising a bottom layer (1), an intermediate layer (2) and a surface layer (3), characterized in that: The bottom layer (1) is a mixture of PVC resin and wood cellulose material, accounting for 30% of the total thickness; the middle layer (2) is a composite layer of nano-anion-rich material and carrier material mixed with PVC resin, accounting for 40% of the total thickness; the middle layer (2) contains a fine microporous structure formed by a foaming process; the surface layer (3) is a mixture of PVC resin, wood cellulose material and functional material, accounting for 30% of the total thickness.

2. The nano-anion composite reinforced PVC wood-plastic board according to claim 1, characterized in that: The lignocellulose material is selected from at least one of wood powder, bamboo powder, rice husk powder, wheat straw powder, coconut shell powder, and cotton stalk powder. The lignocellulose is modified using a silane coupling agent before use. The modification method of the lignocellulose is as follows: The lignocellulose material is dried at a temperature of 80-120°C for 2-4 hours to remove surface moisture, and the lignocellulose material is crushed into fine particles with a particle size controlled between 40-100 meshes. An organic solvent is selected to dissolve the silane coupling agent, and the concentration is controlled between 1% and 5%. The dried lignocellulose material is placed in the silane coupling agent solution and soaked for 10-30 minutes. After soaking, the material is taken out and excess liquid is absorbed with filter paper. The modified lignocellulose material is heated at a temperature of 60-120°C for 1-3 hours to promote the reaction of the silane coupling agent with the hydroxyl group on the surface of the lignocellulose material to form a stable chemical bond.

3. The nano-anion composite reinforced PVC wood-plastic board according to claim 1, characterized in that: The nanometer negative ion material is selected from at least one of tourmaline, tourmaline, zinc oxide, titanium dioxide, nanometer silver, nanometer copper and rare earth elements.

4. The nano-anion composite reinforced PVC wood-plastic board according to claim 1, characterized in that: The carrier material includes at least one of activated carbon, mesoporous silica, zeolite, ceramic powder, cellulose-based material, polyurethane foam, carbon nanotube, graphene, montmorillonite and glass fiber.

5. The nano-anion composite reinforced PVC wood-plastic board according to claim 1, characterized in that: The functional material includes at least one of a photocatalyst, an anti-ultraviolet absorber, an antibacterial agent, a hydrophilic additive, a breathable additive and a conductive material.

6. The nano-anion composite reinforced PVC wood-plastic board according to claim 1, characterized in that: The bottom layer (1) and the surface layer (3) are both provided with microporous structures, the microporous density is 5%-10%, and the microporous diameter is controlled between 10-50 microns.

7. The nano-anion composite reinforced PVC wood-plastic board according to claim 1, characterized in that: The micropore density of the intermediate layer (2) is about 30%-50%, and the micropore diameter is controlled between 1-10 microns.

8. A production process of nano-negative ion composite reinforced PVC wood-plastic board, used for producing the nano-negative ion composite reinforced PVC wood-plastic board according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix the raw materials of the bottom layer (1), the middle layer (2) and the surface layer (3) respectively, and control the temperature of the twin-screw extruder to be between 160° C. and 180° C.; Step 2: Use a co-extrusion device to extrude the materials of the bottom layer (1), the middle layer (2) and the surface layer (3) simultaneously, and form a multi-layer composite sheet through a co-extrusion die. After the molding is completed, cool it to room temperature; Step 3: For the formed bottom layer (1) and surface layer (3), a microporous structure is formed on the surface or inside of the material by laser drilling; Step 4: The formed sheet is trimmed and heat treated. The heat treatment temperature is controlled at about 120°C and the time is 20 minutes.

9. The production process of the nano-anion composite reinforced PVC wood-plastic board according to claim 8, characterized in that: The pressures of different extrusion layers of the co-extrusion equipment are as follows: bottom layer (1): 1-5MPa; middle layer (2): 1-3MPa; surface layer (3): 1-3MPa.

10. The production process of the nano-anion composite reinforced PVC wood-plastic board according to claim 8, characterized in that: The foaming agent used in the middle layer (2) is a composite foaming agent of citric acid and sodium bicarbonate, and the added amount of the foaming agent is 1%-5% of the total amount of raw materials of the middle layer (2).

Citation Information

Cited By

  • Preparation method of green ecological composite wood floor

    CN120326738A